A novel MEREC-MULTIMOOSRAL MADA framework for the strategic selection of edible oils: an optimization model for health sustainability - Balo, Figen; Ulutas, Alptekin (Elsevier Sci Ltd, 2026)
Edible vegetable oils are essential for cooking and play a significant role in the human diet. Their suitability largely depends on fatty acid composition and heat stability. Thermal oxidation, which occurs when oils are heated above their smoke point, can alter chemical structures and has therefore gained increasing attention in food science. This study proposes a novel multiple-attribute decision analysis framework for the strategic evaluation of vegetable oils based on compositional and thermal stability criteria. The framework integrates the objective MEREC method for criteria weighting with the MULTIMOOSRAL method for ranking alternatives. Results from MEREC analysis indicate that polyunsaturated fat content (%) is the most influential criterion affecting the decision matrix. According to the MULTIMOOSRAL ranking, camelina oil emerged as the most suitable alternative among the evaluated oils. Model robustness was confirmed through sensitivity analysis and comparison with CoCoSo and WASPAS methods, which produced highly consistent and strongly correlated rankings.
Keywords: Edible Oils; Health-Oriented Evaluation; Merec; Multimoosral; Plant Oils